Konflik dalam Organisasi - Muqdamien, Birru (Jurnal Literasi Pendidikan Nusantara, 2020)
Consciously or not, conflict can occur anywhere in any situation, an indication that when the communication and information system does not meet its targets, misunderstandings arise between two or more parties. Conflict is a battle to win or lose both between individuals and between groups. Conflict can also have the consequences of triggering war between countries. However, apart from the problem size of the conflict itself, conflict can be resolved in many ways. For example, by using power, confrontation, compromise, peace, and lowering positions